2003
DOI: 10.1177/097215090300400108
|View full text |Cite
|
Sign up to set email alerts
|

Resource Strategy and Signals to Resources Market in Indian Software

Abstract: Resource dependence of strategies of firms in software have mostly been studied from an internal perspective. However, because large manpower turnover takes place across most firms and because quality of resources is uncertain, firms value the functioning of the market of software personnel. Signals based on which transactions in such a market take place appear through advertisements for jobs. This paper has studied 1,615 advertisements for software jobs in India and abroad. It is observed that signals that ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Resources transfers across firm boundaries are logically disallowed then. However, Banerjee (2003a) observed that resources transfers across firm boundaries do take place for strategy coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Resources transfers across firm boundaries are logically disallowed then. However, Banerjee (2003a) observed that resources transfers across firm boundaries do take place for strategy coordination.…”
Section: Introductionmentioning
confidence: 99%